Development of Interactive Multimedia on Electron Configuration Concept - Dzikrika*, Nuuridzdzati; Junanto, Tulus; Erlina, Erlina; Enawaty, Eny; Sasri, Risya; Rasmawan, Rahmat; Nizam, Dinna Nina Mohd (Jurnal Pendidikan Sains Indonesia, 2024)
Interactive multimedia has an important role in the learning process. The interactive multimedia presented the learning material in various forms and supported students understanding of those who have different learning styles. To help students understand the topic and to facilitate students learning style the PeT-EFig is developed. PeT-EFig (periodic table and electron configuration) as interactive multimedia which supported students understanding of electron configuration concepts. The objectives of this study were a) to determine the feasibility of PeT-EFig, and b) to determine the response of chemistry teachers and students of PeT-EFig as interactive multimedia. The research method used is research and development (RD) using the ADDIE model with five stages: analysis, design, and development stages. However, the research was only conducted up to the development stage due to time constraints. Based on the result, PeT-EFig is considered very suitable by the experts with 96 and 95% respectively. Likewise, teachers at SMA Muhammadiyah 1 Pontianak who teach chemistry subjects, stated that they strongly approved PeT-EFig as interactive multimedia on electron configuration 96%. Additionally, students also provided very positive feedback on the PeT-EFig through a small-scale trial involving 15 students with an average percentage of 87% for each aspect. Similarly, when a large-scale trial with 40 students, the final percentage score for each aspect was found to be 87%. The result indicated that the PeT-EFig could assist teachers in delivering the concepts and help students understand the electron configuration and atomic structure